The Foucault Effect in Organization Studies - Raffnsøe, Sverre; Mennicken, Andrea; Miller, Peter (Organization studies, 2019)
Since the establishment of Organization Studies in 1980, Michel Foucault’s oeuvre has had a remarkable and continuing influence on its field. This article traces the different ways in which organizational scholars have engaged with Foucault’s writings over the past thirty years or so. We identify four overlapping waves of influence. Drawing on Foucault’s Discipline and Punish, the first wave focused on the impact of discipline, and techniques of surveillance and subjugation, on organizational practices and power relations. Part of a much wider ‘linguistic’ turn in the second half of the twentieth century, the second wave led to a focus on discourses as intermediaries that condition ways of viewing and acting. This wave drew mainly on Foucault’s early writings on language and discourse. The third wave was inspired by Foucault’s seminal lectures on governmentality towards the end of the 1970s. Here, an important body of international research investigating governmental technologies operating on subjects as free persons in sites such as education, accounting, medicine and psychiatry emerged. The fourth and last wave arose out of a critical engagement with earlier Foucauldian organizational scholarship and sought to develop a more positive conception of subjectivity. This wave draws in particular on Foucault’s work on asceticism and techniques of the self towards the end of his life. Drawing on Deleuze and Butler, the article conceives the Foucault effect in organization studies as an immanent cause and a performative effect. We argue for the need to move beyond the tired dichotomies between discipline and autonomy, compliance and resistance, power and freedom that, at least to some extent, still hamper organization studies. We seek to overcome such dichotomies by further pursuing newly emerging lines of Foucauldian research that investigate processes of organizing, calculating and economizing characterized by a differential structuring of freedom, performative and indirect agency.